EQUATION OF A CIRCLE: (x-h)² + (y-k)² =r²
= (x+1)² + (y-4)² =3
Answer:
(-(7-9))(z)-6z= 8(-6+2)
Simplify
-(-2)(z) -6z =8(-6+2)
Multiply 8*-6 and 8*2
2z -6z= -48+16
Combine like terms
2z+-6z =-32
-4z=-32
Divide both sides by -4
z=8
Step-by-step explanation:
Twice as long as little drop...
8(4x+5)=136
Multiply the number outside of the parenthesis(8) with the numbers inside the parenthesis(4x and 5).
32x+40=136
Subtract 40 from both sides
32x=96
Divide both sides by 32 so the only thing remaining on the side of the variable is only the variable itself.
Final Answer: x= 3